Implementation of Maqasid Al-Syariah in Empowering the Zakah Community Development Program - Andi Martina Kamaruddin; Rabiatul Adawiyah; Khodijah Nur Tsalis; Ahmad Abbas (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
The study investigates the implementation of zakah as a strategy for community empowerment in Gunung Binjai village, Balikpapan city, via the Zakah Community Development (ZCD) system. Utilizing descriptive qualitative methods with a socio-economic approach, the research evaluates the system through maqasid al-syariah. Findings indicate that the ZCD system enhances the welfare of zakah recipients (mustahik) in line with maqasid al-syariah principles, particularly daruriyatul khams, which include protecting religion, life, intellect, progeny, and property. This system significantly improves mustahik socio-economic well-being, illustrating zakah’s role beyond charity as a tool for societal transformation. The study provides empirical evidence and a detailed analysis, highlighting the ZCD system as a model for effective community empowerment and demonstrating the compatibility of Islamic principles with contemporary socio-economic development. It advocates for a holistic approach rooted in maqasid al-syariah to achieve sustainable progress in marginalized communities.